PLA and Organoclays Nanocomposites: Degradation Process and Evaluation of ecotoxicity Using Allium cepa as Test Organism - Souza, Patrícia Moraes Sinohara; Corroqué, Nádia Aline [UNESP]; Morales, Ana Rita; Marin-Morales, Maria Aparecida [UNESP]; Mei, Lucia Helena Innocentini (Springer Nature, 2013)
In this study, nanocomposites of PLA and organoclays Cloisite 20A and Cloisite 30B were prepared by the melt intercalation method and the obtained samples were characterized by transmission electron microscopy (TEM). Since composting is an important proposal to the final disposal of biopolymers, the influence of clays on the hydrolytic degradation process of PLA was evaluated by visual analysis and monitoring of molecular weight after periods of 15 and 30 days of degradation in compost. After degradation of the materials in composting environment, the evaluation of cytotoxic, genotoxic and mutagenic effects of compost aqueous extract was carried out using a bioassay with Allium cepa as test organism. The TEM micrographs permitted the observation of different levels of dispersion, including exfoliated regions. In the evaluation of hydrolytic degradation it was noted that the presence of organoclays can decrease the rate of degradation possibly due to the barrier effect of clay layers and/or the higher degree of crystallinity in the nanocomposite samples. Nevertheless, even in the case of nanocomposites, the molecular weight reduction was significant, indicating that the composting process is favorable to the chain scission of PLA in studied materials. In the analysis performed by the bioassay using A. cepa as test organism, it was found that after degradation of the PLA and its nanocomposites the aqueous extract of compost samples induced a decreasing in the mitotic index and an increasing in the induction of chromosomal abnormalities. These results were statistically significant in relation to the negative control (distilled water). By comparing the results obtained for the nanocomposites in relative to pure polymer, there were no statistically significant differences. The types of the observed chromosomal aberrations indicated a possible genotoxic effect of the materials, which may be related to an aneugenic action of PLA degradation products. © 2013 Springer Science+Business Media New York.
Keywords: Allium cepa; Bioassay; Composting; Ecotoxicity; Nanocomposites; Organoclays; PLA